2004
DOI: 10.1063/1.1804602
|View full text |Cite
|
Sign up to set email alerts
|

Capillary filling speed of water in nanochannels

Abstract: The capillary filling speed of water in nanochannels with a rectangular cross section and a height on the order of 100nm has been measured over a length of 1cm. The measured position of the meniscus as a function of time qualitatively follows the Washburn model. Quantitatively, however, there is a lower than expected filling speed, which we attribute to the electro-viscous effect. For demineralized water in equilibrium with air the elevation of the apparent viscosity amounts up to 24±11% in the smallest channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
244
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(265 citation statements)
references
References 18 publications
16
244
3
2
Order By: Relevance
“…The validity of Eq. (1) has been reported, even in a glass channel with a 5-nm depth (Tas et al 2004). It was also reported that water permeation in concrete can be evaluated with Eq.…”
Section: Calculation Of the Permeation Ratementioning
confidence: 95%
“…The validity of Eq. (1) has been reported, even in a glass channel with a 5-nm depth (Tas et al 2004). It was also reported that water permeation in concrete can be evaluated with Eq.…”
Section: Calculation Of the Permeation Ratementioning
confidence: 95%
“…The position of the moving meniscus in nanochannels as a function of time has been modeled ͑Washburn, 1921; Tas et al, 2004͒, but after a certain filling length, the formation of bubbles by the enclosure of air is typically encountered, a problem that has been addressed ͑Han, Riehn and Austin, 2006͒. For capillary filling studies, the behavior of liquid in shallow nanochannels down to 6 nm can be monitored with a Fabry-Perot interferometer by measuring the refractive index of the medium inside the channel ͑Delft et al,…”
Section: B Electrokinetic Effects In Nanochannelsmentioning
confidence: 99%
“…5,6 An extremely large slip length (micrometre order) inside a very small tube (nanometre order) indicates a nearly flat velocity profile, in contrast to the Hagen-Poiseuille flow model. On the other hand, experiments have also shown an increased flow resistance in nanocapillary filling, 8,9 and the explanation of this increased resistance in nanochannel is not clear either. 9,10 In order to build functional and practical nanofluidic devices, it is also important to know the velocity profile, which plays an key role for transport phenomenon and separation in nanofluidics, due to, e.g.…”
Section: Introductionmentioning
confidence: 95%